2019
DOI: 10.1007/s10113-019-01519-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variability in Terminos Lagoon (Mexico) waters during the 2009–2010 drought reveals upcoming trophic status shift in response to climate change

Abstract: The 2009-2010 El Niño was accompanied by a severe drought strongly impacting Mexico as well as Central America, the Caribbean, and the southern USA. The present work aims at assessing how such a major climatic event impacted the hydrological typology of transitional waters in Terminos Lagoon, one of the largest shallow tropical lagoons fringing the Gulf of Mexico. Spatiotemporal inter-comparison of hydrological conditions was conducted by pairing a reference multiparametric dataset (14 hydrological parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…In this study, the combination of PCA and KW analysis, allowed us to confirm our hypothesis, this is, that there are spatiotemporal differences between samplings, generated by the high hydrological variability in Términos lagoon Fichez et al, 2019). These differences are explained by the variation and interaction of different parameters in each sampling.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…In this study, the combination of PCA and KW analysis, allowed us to confirm our hypothesis, this is, that there are spatiotemporal differences between samplings, generated by the high hydrological variability in Términos lagoon Fichez et al, 2019). These differences are explained by the variation and interaction of different parameters in each sampling.…”
Section: Discussionsupporting
confidence: 74%
“…However, the most frequently referred classification for TL divides it into two main regions: (1) East zone, related to marine conditions, i.e., high salinity and low nutrient concentrations, and (2) West zone, where the Palizada river has notorious influence such as high nutrient and organic matter concentrations Fichez et al, 2019). This zonation though does not exhibit a time-space consistency, and indicate that these regions behave almost as independent water bodies if the epicontinental water discharges into the lagoon do not increase significantly because they generate the hydrological homogenization of the lagoon.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may reflect the influence of environmental variables at each site as it has been observed elsewhere (Frankovich et al, 2006;Kelly et al, 2009), and whose variability is very high in coastal ecosystems (Day et al, 2013). Terminos lagoon exhibits high temporal and spatial variations (Fichez et al, 2019;Guerra-Santos & Kahl, 2018) and usually is divided in zones related to the influence of surrounding systems. However it has been observed that these zones are not constant and that the lagoon presents a series of environmental gradients which vary spatially and temporally (López-Mejía et al, 2022).…”
Section: Discussionmentioning
confidence: 90%